Use of Tick Cell Lines in Co-Infection Studies with a Preliminary Study of Co-Culture of Borrelia burgdorferi and Anaplasma phagocytophilum - Zając, Violetta; Bell-Sakyi, Lesley; Wójcik-Fatla, Angelina (Pathogens (Basel), 2025)
Ixodes ricinus is an important vector of infectious human and livestock diseases in Europe. Co-infections of pathogens in ticks and hosts have been reported. Tick cell lines offer a useful model system for study of co-infections. We present a review of the existing literature on co-infections in tick cell lines. Previous studies have demonstrated the usefulness of tick cell lines in studies on co-infection of different pathogens and their interaction with the tick microbiome. We also carried out a preliminary study to investigate the effects of co-culturing Borrelia burgdorferi and Anaplasma phagocytophilum on their growth and interactions with the Ixodes ricinus cell line IRE/CTVM19 over a 13-day period. Replication of both pathogens was quantified by real-time PCR. The presence of A. phagocytophilum appeared to have a slight inhibitory effect on the multiplication of B. burgdorferi, that were added subsequently. In contrast, the prior presence of B. burgdorferi appeared to have a stimulatory effect on A. phagocytophilum after 6 days in culture. We conclude that the IRE/CTVM19 tick cell line is suitable for simultaneous and continuous cultivation of both bacteria and can be applied in future research.